Exploring EMDR: an innovative approach with Posner Paradigm to reprocessing negative memories in a non-clinical sample - Piccardi, Laura; Russo, Samuele; Lasaponara, Stefano; Boccia, Maddalena; Riso, Chiara; Tizzani, Emanuela; Burrai, Jessica; Giannini, Anna Maria; Guariglia, Paola (Frontiers in Psychiatry, 2025)
IntroductionEye Movement Desensitization and Reprocessing (EMDR) is a structured psychotherapy primarily focused on treating individuals who have experienced distressing, traumatic events and other mental disorders. While traditionally associated with bilateral eye movements, the underlying mechanisms of EMDR remain a topic of interest. Our goal was to explore whether an endogenous attention task, specifically the Posner paradigm, which involves shifting spatial attention without eye movements, could be as effective as the conventional eye movements in processing distress memories of moderate to high intensity and provide insights into the underlying mechanisms of the technique.MethodsTo achieve this, we conducted a randomized controlled trial involving 50 healthy participants, who were divided into two groups (EMDR and other engaging in Posner paradigm). Participants were tasked with recalling distress memories while undergoing their respective interventions. We measured the overall effects of both approaches on subjective units of distress (SUDs), the Impact of Event Scale-Revised (IES-R), and the Posttraumatic Stress Disorder Checklist for DSM-5 (PCL-5). Pre- and post-intervention assessments were conducted to evaluate changes in these measures.ResultsOur results indicated that both the EMDR and Posner groups experienced significant reductions in scores on the SUDs, IES-R, and PCL-5, demonstrating equal effectiveness in alleviating distress associated with distress memories. Notably, the results suggest that the mechanism of attention shifting, rather than the specific modality of eye movements, plays a critical role in the therapeutic process.ConclusionThese data suggest that endogenous visuospatial tasks, such as those employed in the Posner paradigm, may serve as viable alternatives to traditional eye movements in EMDR therapy. Furthermore, our findings indicate that the simultaneous presentation of stimuli may not be a crucial aspect of EMDR’s effectiveness. This study contributes to the understanding of EMDR by highlighting the importance of attentional processes in memory processing and opens avenues for further research into alternative therapeutic techniques that leverage cognitive mechanisms. However, as this study employed a non-clinical sample of healthy participants with distress memories, caution is warranted when generalizing these findings to clinical populations with diagnosed trauma-related disorders. The implications of these findings are discussed within the broader theoretical frameworks of EMDR and attentional involvement, emphasizing the potential for integrating cognitive tasks into trauma-focused therapies.